LINC00665 up-regulates SIN3A expression to modulate the progression of colorectal cancer via sponging miR-138-5p - Shoushan Nan; Shuangxia Zhang; Rong Jin; Juelei Wang (Cancer Cell International, 2022)
Abstract Background Colorectal cancer (CRC) is a malignant tumor affecting people worldwide. Long noncoding RNAs (lncRNAs) is a crucial factor modulating various cancer progression, including CRC. Long intergenic non-protein coding RNA 665 (LINC00665) has been proven as an oncogene in several cancers, but its function in CRC is still unclear. Methods QRT-PCR was performed for RNA quantification. Functional assays were designed and carried to test cell phenotype while mechanism experiments were adopted for detecting the interaction of LINC00665, microRNA-138-5p (miR-138-5p) and SIN3 transcription regulator family member A (SIN3A). In vivo experiments were conducted to test LINC00665 function on modulating CRC tumor progression. Results LINC00665 displayed high expression in CRC tissues and cells, and promoted tumor progression in vivo. MiR-138-5p displayed abnormally low expression in CRC, and was verified to be sponged by LINC00665. Furthermore, SIN3A, as the downstream mRNA of miR-138-5p, exerted promoting impacts on CRC cells. Rescue experiments certified that overexpressed SIN3A or silenced miR-138-5p could offset the repressed function of LINC00665 knockdown on CRC progression. Conclusions LINC00665 could sponge miR-138-5p to up-regulate SIN3A expression, thus accelerating CRC progression. Graphic abstract